2015
DOI: 10.1111/bjd.13351
|View full text |Cite
|
Sign up to set email alerts
|

A national study on adherence to a basal cell carcinoma guideline; development of a tool to assess guideline adherence

Abstract: The findings emphasize the importance of direct feedback to practitioners regarding adherence. Furthermore, together with existing frameworks, the method described could be used by developers in a guideline update to identify and anticipate barriers to successful implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…This is probably also the case in the current study. The poor adherence in high-risk BCCs is in line with the results of another study in the Netherlands, in which self-reported BCC guideline adherence with respect to excision margins was 37.9% (7).…”
Section: Discussionsupporting
confidence: 85%
“…This is probably also the case in the current study. The poor adherence in high-risk BCCs is in line with the results of another study in the Netherlands, in which self-reported BCC guideline adherence with respect to excision margins was 37.9% (7).…”
Section: Discussionsupporting
confidence: 85%
“…Adherence to guidelines was based on 2 AUDIT-checklists for BCC and SCC, respectively (Appendices S1 and S2 1 ). The 16-item checklist for BCC was based on a previously developed and tested checklist (19). The 21-item checklist used for SCC was newly developed using the same principles as the BCC checklist.…”
Section: Management Decisionmentioning
confidence: 99%
“…Macroscopicamente, os CBCs são lesões de caráter assintomático e lenta progressão, apresentam aspecto perolado e telangiectasias (melhor visualizados com o auxílio do dermatoscópio), ao exame dermatológico apresentam-se ovóides, cinzaazulados, áreas tipo folha de bordo, áreas em raio de roda, ulceração e vasos arboriformes. Sua classificação clínica é dividida em nódulo-ulcerativo, superficial, pigmentado, esclerodermiforme e fibroepitelioma de Pinkus (Aguiar et al, 2017;Borgonjen et al, 2015).…”
Section: Discussionunclassified